Geologic analysis of naturally fractured reservoirs - Nelson, Ronald A. (Gulf Professional Pub., 2001)
Geologists, engineers, and petrophysicists concerned with hydrocarbon production from naturally fractured reservoirs will find this book a valuable tool for obtaining pertinent rock data to evaluate reserves and optimize well location and performance. Nelson emphasizes geological, petrophysical, and rock mechanics to complement other studies of the subject that use well logging and classical engineering approaches. This well organized, updated edition contains a wealth of field and laboratory data, case histories, and practical advice. A great how-to-guide for anyone working with fractured or highly anisotropic reservoirs Provides real-life illustrations through case histories and field and laboratory data.